2013
DOI: 10.1111/jch.12118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nebivolol on Aortic Compliance in Patients With Diabetes and Maximal Renin Angiotensin System Blockade: The EFFORT Study

Abstract: The beneficial effects of nebivolol on arterial stiffness and endothelial dysfunction are well documented in untreated hypertensive patients and differ from nonvasodilatory bblockers. This study tests the hypothesis that the addition of nebivolol in predominantly African American patients with type 2 diabetes already receiving maximally tolerated doses of renin-angiotensin system (RAS) blockers will further improve large artery compliance. Patients with type 2 diabetes and hypertension on maximal RAS blockade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Finally, in AA patients with stage 1 hypertension, nebivolol monotherapy increased flow‐mediated dilation and improved arterial wave reflections compared with untreated patients . In contrast, no differences between metoprolol succinate and nebivolol were observed in aortic compliance indices in a largely AA population of diabetics …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Finally, in AA patients with stage 1 hypertension, nebivolol monotherapy increased flow‐mediated dilation and improved arterial wave reflections compared with untreated patients . In contrast, no differences between metoprolol succinate and nebivolol were observed in aortic compliance indices in a largely AA population of diabetics …”
Section: Discussionmentioning
confidence: 86%
“…50 In contrast, no differences between metoprolol succinate and nebivolol were observed in aortic compliance indices in a largely AA population of diabetics. 51 Moreover, these experiments were performed in the setting of prostacyclin inhibition. The contribution of the prostacyclin pathway was thus not investigated in this study and may also potentially be affected by b-blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Терапия небивололом больных АГ и СД 2-го типа приводила к достоверному снижению САД и ДАД, уменьшению гликемии, показателей общего холестерина и холестерина липопротеидов низкой плотности [20]. У больных АГ с СД добавление к базисной терапии метопролола сукцината приводило к достоверному увеличению уровня гликозилированного гемоглобина, а при использовании небиволола данный показатель не изменялся [21].…”
Section: небивололу присущи следующие благоприятные гемодинамические unclassified
“…Compared with metoprolol, nebivolol reduces plasma ADMA levels and the augmentation index (AIx) [ 20 ], a surrogate measure of arterial stiffness that is also associated with cardiovascular risk [ 21 ]. However, the AIx benefits compared with metoprolol may not extend to individuals with hypertension and diabetes mellitus who are receiving maximal tolerated doses of renin-angiotensin-aldosterone system (RAAS) blockers [ 22 ]. Of note, a 12-month randomized trial that compared the effects of nebivolol and metoprolol on a number of hemodynamic and biochemical parameters found no difference in AIx and ADMA levels between the two groups, but demonstrated that only nebivolol had a beneficial effect on oxidative stress [ 23 ] and significantly reduced central systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), and left ventricular wall thickness [ 24 ].…”
Section: Endothelial and Hemodynamic Effectsmentioning
confidence: 99%